Adaptación al cambio climático y la gestión del riesgo en comunidades del río Tempisque, Costa Rica (Tema Central) - Gutiérrez Miranda, Marcela (2021)
The actions carried out by the academy are analyzed to contribute to local management improvement through the implementation of climate change adaptation mechanisms and risk management in three communities in the Lower Tempisque River Basin in Costa Rica. The project uses participatory action research as a methodology, involving the various actors and generating changes in them. The main result shows that the actions carried out in: environmental education, waste collection campaigns, deforestation, rural tourism, among others, have contributed to increasing the sense of care and environment preservation in the people of the community, through the understanding of the relationship that exists between the ecosystem conservation and the living conditions improvement in the communities. In addition, it is evident how climate variability affects economic development since it affects the productive capacity area and how the project multidisciplinary approach directly affects the ecosystem conservation and the communities' development.